ANALISIS PERILAKU KONSUMEN YANG MEMPENGARUHI PEMILIHAN TEMPAT WISATA PANTAI DENDANG MELAYU BATAM - Muhammad Rasyid Ridho Lubis; Dwi Kartikasari (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
Dendang Melayu Beach is a public beach that is being developed by the Batam City Government. Although various efforts have been made by the government to increase the number of visitors to this beach, it turns out that the number of visitors has not necessarily increased consistently but fluctuated up and down. Therefore, this research was carried out to further explore the behavior of visitors in the hope that it could become a material evaluation of the government in developing this tourist attraction. This study aims to examine the effect of consumer behavior on the selection of Dendang Melayu Beach tourist attractions. The respondents of this study were 100 tourists who visited the Batam Dendang Beach. The data analysis method used is inductive statistics using multiple linear regression. The results of this study are the four variables of consumer behavior namely cultural, social, personal and psychological factors partially positive and significant effect on the choice of tourist attractions.